Tingkat Kepercayaan Diri Atlet Panahan NPC Kota Bandung - Langgeng, Langgeng; Rohendi, Aep; Hardi, Veny Juniarni (Jurnal Kepelatihan Olahraga, 2023)
Trust is a psychological factor that can have a significant effect on athletic performance. This includes the athlete's personal belief in his abilities and skills, belief in the coach and team members, and belief in the strategy and game plan. The purpose of this study was to determine the level of confidence of NPC archery athletes in Bandung City. The research method used in this study is descriptive- quantitative. This method is used to obtain data from the answers to the questionnaire. The population in this study was NPC archery athletes in Bandung City, totaling 13 athletes. The results of this study showed that the confidence level of the Bandung City NPC archery athletes was 65.38%, which means that most of the Bandung City NPC archery athletes had a good level of self-confidence. Thus, confidence plays an important role in everyday life, training, and when competing. In addition to playing an important role, the results of this level of confidence can serve as a guide so that the level of an athlete's confidence can be applied or increased.